Effect of Tumor Suppressor MiR-34a Loaded on ZSM-5 Nanozeolite in Hepatocellular Carcinoma: In Vitro and In Vivo Approach - Salah, Zeinab; Abd El Azeem, Eman M.; Youssef, Hanan F.; Gamal-Eldeen, Amira M.; Farrag, Abdel R.; El-Meliegy, Emad; Soliman, Bangly; Elhefnawi, Mahmoud (Current Gene Therapy, 2019)
Background: MicroRNA modulation therapy has shown great promise to treat hepatocellular carcinoma (HCC), however Efficient tissue-specific and safe delivery remains a major challenge. Objective: We sought to develop an inorganic-organic hybrid vehicle for the systemic delivery of the tumor suppressor miR-34a, and to investigate the efficiency of the delivered miR-34a in the treatment of HCC in vitro and in vivo. Methods: In the present study, pEGP-miR cloning and expression vector, expressing miR-34a, was electrostatically bound to polyethyleneimine (PEI), and then loaded onto ZSM-5 zeolite nanoparticles (ZNP). Qualitative and quantitative assessment of the transfection efficiency of miR-34a construct in HepG2 cells was applied by GFP screening and qRT-PCR, respectively. The expression of miR-34a target genes was investigated by qRT-PCR in vitro and in vivo. Results: ZNP/PEI/miR-34a nano-formulation could efficiently deliver into HepG2 cells with low cytotoxicity, indicating good biocompatibility of generated nanozeolite. Furthermore, five injected doses of ZNP/PEI/miR-34a nano-formulation in HCC induced male Balb-c mice, significantly inhibited tumor growth, and demonstrated improved cell structure, in addition to a significant decrease in alphafetoprotein level and liver enzymes activities, as compared to the positive control group. Moreover, injected ZNP/PEI/miR-34a nano-formulation led to a noticeable decrease in the CD44 and c-Myc levels. Results also showed that ZNP/PEI/miR-34a nano-formulation inhibited several target oncogenes including AEG-1, and SOX-9, in vitro and in vivo. Conclusion: Our results suggested that miR-34a is a powerful candidate in HCC treatment and that AEG-1 and SOX-9 are novel oncotargets of miR-34a in HCC. Results also demonstrated that our nano-formulation may serve as a candidate approach for miR-34a restoration for HCC therapy, and generally for safe gene delivery.
Keywords: gene delivery